Social Economic Factor and Readability to Higher Education: The Mediating Role of Learning Achievement - Shendy Andrie Wijaya; Yusita Titi Hapsari (Universitas Negeri Malang, 2021)
Understanding determinant factors affecting students interest in higher education will promote a greater human resource. This study aims to investigate the impact of the social-economic conditions of the fishing community in Jember of Indonesia on students’ intention to higher education, as well as understanding the role of learning achievement. This study involved 110 completed questionnaires for analysis purposes. Furthermore, the data were analyzed using a path analysis model. The results of this study indicate an impact of the social economic conditions of the fishing community on students’ intention to higher educations. This study can be concluded that social economic conditions and their learning achievement perform students’ interest in higher education. This study also notes that learning achievement has successfully mediated the relationship between social-economic and interest to higher students.Keywords: Social economic, Students’ achievement, Intention to higher education